Relative exchangeable copper: A promising tool for family screening in Wilson disease - Trocello, Jean-Marc; El Balkhi, Souleiman; Woimant, France; Girardot-Tinant, Nadège; Chappuis, Philippe; Lloyd, Carla; Poupon, Joël (Movement disorders, 2014)
ABSTRACT Background Family screening is a main step for the diagnosis in Wilson disease. This study was undertaken to evaluate the value of relative exchangeable copper for family screening. Methods Data from family screening were collected from the French National Center of Reference for Wilson disease. Subjects who were first‐ or second‐degree relatives of the index case underwent clinical examination and biological parameters. Results Of 127 subjects examined, copper abnormalities or low ceruloplasminemia were detected in 21 subjects, corresponding to 5 patients with Wilson disease, 14 heterozygous ATP7B carriers and 2 subjects with no ATP7B mutations. Relative exchangeable copper determination significantly discriminates heterozygous ATP7B carriers and subjects with no ATP7B mutations from WD patients with a cutoff of 15%. Conclusions Exchangeable copper appears to be a promising tool for family screening in Wilson disease. © 2013 International Parkinson and Movement Disorder Society